Rhabdomyomatous mesenchymal hamartoma presenting as telangiectasia in a 57‐year‐old man. (4th June 2021) - Zargari, Omid; Asadi, Masih; Azimi, Seyyede Zeinab; Mesbah, Alireza
Abstract: Rhabdomyomatous mesenchymal hamartoma (RMH) is a rare congenital malformation of the dermis and subcutaneous tissue. Usually, RMH occurs in the midline of the face and neck region. We described a case of RMH presenting as telangiectasia in a 57‐year‐old man with a history of pityriasis lichenoides chronicus. Histopathological examination revealed a subepidermal haphazard proliferation of striated muscular tissue perpendicular to the epidermis. These bundles of striated muscular tissue were admixed with adnexal structures. The diagnosis was consistent with RMH. RMH is more common in the neonatal period or in young children, but we should consider it as part of a differential diagnosis in older adults as well.